2022
DOI: 10.1109/tasc.2022.3159507
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Fiber Optic Sensing to Identify Locations of Resistive Transitions in REBCO Conductors and Magnets

Abstract: High-temperature superconductors such as REBa2Cu3O7-x (REBCO, RE = rare earth) can generate strong magnetic fields that are promising for applications in particle accelerators and compact fusion reactors. Traditionally, voltage taps are installed in superconducting magnets to measure the voltage signals due to resistive transitions. The voltage-tap-based diagnostics is important for the development of magnet technology as it can help pinpoint the locations in the magnet windings that limit the magnet performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The experiment with the optic fiber demonstrated that the fiber can operate at 4.2 K. A successful impregnation technique will benefit future tests of the optic fiber toward identifying the hot spots along rebco cables [73] and ultimately the detection of normal transitions [74,75].…”
Section: Continue Developing Magnets Using Star® Wires Toward Higher ...mentioning
confidence: 99%
“…The experiment with the optic fiber demonstrated that the fiber can operate at 4.2 K. A successful impregnation technique will benefit future tests of the optic fiber toward identifying the hot spots along rebco cables [73] and ultimately the detection of normal transitions [74,75].…”
Section: Continue Developing Magnets Using Star® Wires Toward Higher ...mentioning
confidence: 99%
“…The research on the bending performance of CORC cable verifies that it has good bending flexibility [19][20][21]. On the research of quenching detection, distributed optical fiber and ultrasonic detection method are used to monitor the state of CORC cable, which can ensure the safety of its operation [22,23]. The research of its axial tensile properties found that the spring structure of the CORC cable makes its tensile strain limit exceed that of HTS tape, and the tensile strain limit of the optimized cable exceeds 10 times of that of HTS tape [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In tokamaks, the large magnet inductances and fast ramp rates complicate protection with traditional sample voltage measurements. Several efforts have shifted toward temperature-based protection, including optical fibers [16][17][18][19] , active acoustic thermometry 20 , and co-wound superconducting wires optimized to act as a thermal switch [21][22][23] . Marchevsky et al 24 demonstrated quench detection in a slit ReBCO tape based on magnetic field changes associated with current redistribution, that was later demonstrated between tapes of a single CORC ® wire 25 and between cables of a CORC ® CICC 26 .…”
mentioning
confidence: 99%